The Axillary View Typically Does Not Contribute to Decision Making in Care for Proximal Humeral Fractures - Berkes, Marschall B. (HSS J, 2015)
BACKGROUND: Convention dictates that an axillary view be obtained when evaluating proximal humerus fractures (PHF). However, the axillary view is frequently omitted because of pain and technical considerations. Furthermore, its diagnostic utility is unclear in this setting. QUESTIONS/PURPOSES: The purpose of this study was to (1) determine the rate of obtaining an adequate axillary X-ray and complete shoulder series at a level I trauma center, (2) understand the cost of ordering and attempting an axillary radiograph, and (3) determine if axillary radiographs influence the management of PHF. PATIENTS AND METHODS: PHF treated between 2009 and 2011 that were ordered for an AP, scapular Y, and axillary view was identified. The types of radiographs actually obtained were recorded. The cost of obtaining three views and a single view of the shoulder with X-ray was determined. Lastly, three surgeons reviewed 42 PHF, both with and without an axillary view (AV), and treatment recommendations were compared. RESULTS: 30% of PHF in this series had an adequate axillary view, and 14% received a complete trauma series. No factors could be identified that were associated with successfully obtaining an axillary view. Reviewers demonstrated substantial intraobserver reliability (κ = 0.759–0.808) regarding treatment recommendations for PHF with and without the axillary view. The addition of the AV had minimal influence on treatment recommendations. CONCLUSION: Considering that the axillary view for PHF is painful, labor-intensive, costly, and does not appear to provide additional diagnostic value, orthopedic surgeons can consider foregoing the use of the axillary view when evaluating and treating PHF, particularly if other advanced imaging is utilized. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11420-015-9445-9) contains supplementary material, which is available to authorized users.